Tafsir Al-Qur’an Al-Karim Karya MUI Sul-Sel - Mursalim Mursalim (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
Tafsir Bugis, which compiled by the Indonesian Ulema Council (MUI), existed within South Sulawesi among Bugis people to fill the lack of literature in Bugis area; therefore, the Qur'an can be understood by ordinary people who do not understand or know Latin language (i.e. Malay) or Arabic interpretation. This includes commentary Tafsir al-Qur'an Bugis completed a 30 chapters written by Bugis interpretation AG. Daud Ismail. The methodology of the tafsir is using the tahlily method through textual forms and the way its construction is not very merely affiliated schools of philosophy and its schools of fiqh.